2013
DOI: 10.1002/app.40079
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and biodegradation behavior of poly(butylene adipate‐co‐terephthalate)/clay nanocomposites

Abstract: Poly(butylene adipate-co-terephthalate) (PBAT) nanocomposites films are prepared by a solution intercalation process using natural montmorillonite (MMT) and cetyltrimethylammonium bromide (CTAB)-modified montmorillonite (CMMT). Cation exchange technique has been used for modification of MMT by CTAB and characterized by Fourier transform infrared analysis, thermo-gravimetric analysis, and X-ray diffraction (XRD) studies. CMMT gives better dispersion in the PBAT matrix than MMT and is confirmed by XRD and transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…They reported that nanocomposites exhibit non-cytotoxicity, non-negative hemostatic effects after contact with blood, higher in vitro hemocompatibility than neat PBAT. Mondal et al [105] modified the MMT by cetyltrimethylammonium bromide (CMMT) and prepared the PBAT/CMMT nanocomposites via solution intercalation process. They observed that PBAT/CMMT shows antimicrobial property due to the intercalated morphology and the presence of quaternary ammonium cation in the CMMT of nanocomposites (Fig.…”
Section: Applicationmentioning
confidence: 99%
“…They reported that nanocomposites exhibit non-cytotoxicity, non-negative hemostatic effects after contact with blood, higher in vitro hemocompatibility than neat PBAT. Mondal et al [105] modified the MMT by cetyltrimethylammonium bromide (CMMT) and prepared the PBAT/CMMT nanocomposites via solution intercalation process. They observed that PBAT/CMMT shows antimicrobial property due to the intercalated morphology and the presence of quaternary ammonium cation in the CMMT of nanocomposites (Fig.…”
Section: Applicationmentioning
confidence: 99%
“…Food pathogenic bacteria such as B. subtilis and S. aureus were used for testing the antimicrobial activity of the films. For the qualitative measurement of antimicrobial activity, disks with a diameter = 11 mm were cut from film samples and the antimicrobial activity was assessed using a modified agar diffusion assay (disk test; Mondal and others ). The plates were observed for possible clear zones after keeping them for incubation at 37 ºC for 2 d. The presence of any clear zone that appeared around the film disk on the plate medium was noted as an indicator of inhibition against the microbial species.…”
Section: Methodsmentioning
confidence: 99%
“…The primary objective of this current study is to develop PBAT‐based nanocomposite films incorporated with SB as an antimicrobial agent and also to study their effectiveness against 2 food pathogenic bacteria, Bacillus subtilis and S. aureus . First, we prepared organically modified clay (cetyltrimethylammonium‐modified MMT [CMMT]), which also acts as an antimicrobial active agent (Mondal and others ). Subsequently, we compared the antimicrobial activities of PBAT/CMMT/SB nanocomposite and PBAT/SB films using the zone of inhibition method and growth curves of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The standard composition of the compost was used as reported in the literature (Mondal et al 2014;Maiti et al 2011;Singh et al 2003). g-HPMC 6 (M) film was prepared and the experiment was carried out for up to 4 weeks.…”
Section: Biodegradation Studymentioning
confidence: 99%
“…The synthesised copolymer was characterised in detail, along with the swelling and deswelling characteristics in simulated conditions. A cell viability study was carried out using stem cells, and the biodegradability of g-HPMC (M) was studied using a compost method (Mondal et al 2014). Finally, ornidazole, an antiangiogenic drug, which is used in Crohn's disease (Rutgreets et al 2005), was selected, and the potential of g-HPMC (M) as a matrix for the in-vitro release of ornidazole as well as the stability of the drug (up to 3 months) was studied.…”
Section: Introductionmentioning
confidence: 99%